'A Course of Severe and Arduous Trials' Bacon, Beckett and Spurious Freemasonry in Early Twentieth-Century Ireland - Brunet, Lynn (Reimagining Ireland, 2009)
The artist Francis Bacon (1909-1992) and the writer Samuel Beckett (1906-1989) both convey in their work a sense of foreboding and confinement in bleak, ritualistic spaces. This book identifies many similarities between the spaces and activities they evoke and the initiatory practices of fraternal orders and secret societies that were an integral part of the social landscape of the Ireland experienced by both men during childhood. Many of these Irish societies modelled their ritual structures and symbolism on the Masonic Order. Freemasons use the term 'spurious Freemasonry' to designate those rituals not sanctioned by the Grand Lodge. The Masonic author Albert Mackey argues that the spurious forms were those derived from the various cult practices of the classical world and describes these initiatory practices as 'a course of severe and arduous trials'. This reading of Bacon's and Beckett's work draws on theories of trauma to suggest that there may be a disturbing link between Bacon's stark imagery, Beckett's obscure performances and the unofficial use of Masonic rites.